High-Entropy Rock-Salt Surface Layer Stabilizes the Ultrahigh-Ni Single-Crystal Cathode - Xu, Zhongxing; Chen, Xinghan; Fan, Wenguang; Zhan, Minzhi; Mu, Xulin; Cao, Hongbin; Wang, Xiaohu; Xue, Haoyu; Gao, Zhihai; Liang, Yongzhi; Liu, Jiajie; Tan, Xinghua; et al. (ACS nano, 2024)
Single-crystalline Ni-rich layered oxides are one of the most promising cathode materials for lithium-ion batteries due to their superior structural stability. However, sluggish lithium-ion diffusion kinetics and interfacial issues hinder their practical applications. These issues intensify with increasing Ni content in the ultrahigh-Ni regime (≥90%), significantly threatening the practical viability of the single-crystalline strategy for ultrahigh-Ni layered oxide cathodes. Herein, by developing a high-entropy coating strategy, we successfully constructed an epitaxial lattice-coherent high-entropy rock-salt layer (∼3 nm) via Zr and Al doping on the surface of the single-crystalline cathode LiNi0.92Co0.05Mn0.03O2 through an in situ modification process. The surface high-entropy rock-salt layer with tailored Ni valence and lattice coherence not only greatly improves lithium-ion diffusion kinetics but also suppresses interface parasitic reactions and surface structural degradations. The high-entropy surface layer-stabilized ultrahigh-Ni single-crystalline cathode (SC-Ni92-ZA) demonstrates significantly improved rate and cycling performances (127.5 mAh g–1 at 20C, capacity retention of 74.9% after 500 cycles at 1C) in a half-cell. The SC-Ni92-ZA exhibits a capacity retention of 87.1% after 600 cycles at 1C in a full-cell. This epitaxial lattice-coherent high-entropy coating strategy develops a promising avenue for developing high-capacity, long-life cathode materials.